Study on photobleaching of methylene blue doped in PMMA, PVA and gelatin using photoacoustic technique - Mat Yunus, W. Mahmood; Chan, Kok Sheng; W. Yunus, Wan Md. Zin (World Scientific Publishing Co. Pte Ltd, 2003)
The photobleaching of Methylene blue embedded in the solid matrix PMMA (poly(methylmethacrylate)), PVA (poly(vinyl alcohol)) and gelatin has been investigated using a photoacoustic technique. Photoacoustic signals were measured as a function of time, chopping frequency, and the beam power. Experimental results indicate that the photobleaching rate is proportional to the incident laser power (260-300 mW) and decreased with increasing the concentration of dopant molecules. Methylene blue embedded in PVA shows the highest photobleaching rate then followed by gelatin and PMMA. The increase of photobleaching rate in PVA is also noticed when the beam power is increased. The thermal diffusivity values obtained for bleached PMMA, PVA and gelatin are 1.46 × 10-3 cm2/s, 0.83 × 10-3 cm2/s and 1.10 × 10-3 cm2/s respectively. Spectrophotometer and Raman spectroscopy were used to confirm the photoacoustic results.